TRACER DIFFUSION OF POTASSIUM, RUBIDIUM, AND CESIUM IN A SUPERCOOLED JADEITE MELT - Roselieb K.; Jambon A. (My University, 1997)
Tracer diffusion coefficients of K, Rb, and Cs were determined in a supercooled jadeite melt using the thin source technique. Experiments were performed at temperatures between 800 and 1020°C at 1 bar pressure. Run times ranged from 5 min to 26 days. Diffusion profiles were measured using the electron microprobe and diffusion coefficients were found to be independent of the amount of tracer initially deposited on the sample surface. Variation of the run times yielded identical diffusivities within experimental error. The dependence of the diffusivity D with temperature T can be described with an Arrhenian equation D = D0exp(-Ea/RT). A least squares fit yields DK = 5.7 . 10-6exp(-127/RT), DRb = 5.9 . 10-6exp(-163/RT), and DCs = 2.0 . 10-4exp(-243/RT), with D0 in m2/s and Ea in kJ/mol. The diffusivity decreases with increasing ionic radius while the activation energy increases. Along the composition join silica-jadeite, similar diffusivities are exhibited by albite and jadeite compositions, whereas diffusivity in silica appears to be up to 2 orders of magnitude lower. The activation energies of K and Rb reveal a minimum at albite composition and a maximum for Cs, whereas the activation energy of Na decreases continously with increasing Al/Si ratio. When compared with neutral species, alkalies with the same radius exhibit higher activation energies.